Wednesday

April 1, 2015

April 1, 2015

Posted by **Olivia** on Sunday, March 10, 2013 at 1:46pm.

- Mathematics. Geometric sequences. -
**Reiny**, Sunday, March 10, 2013 at 3:25pma = 2 , r = 2

sum(n) = 2(2^n - 1)/(2-1) = 2(2^n - 1)

= 2^(n+1) - 2

sum(n+1) = 2(2^(n+1) - 1)/1 = 2(2^(n+1) - 1)

= 2^(n+2) - 2

sum(N+1) - sum(n) =2^(n+2) - 2 - (2^(n+1) - 2)

= 2^(n+2) - 2^(n+1)

= 2^(n+1) (2 - 1)

= 2^(n+1) , which is a positive number

so sum(n) < sum(n+1)

**Answer this Question**

**Related Questions**

Maths - 1..The first 2 terms of a geometric progression are the same as the ...

Math *URGENT - Please give the answers and solutions for each. 1.If the second ...

math - in an arithmetic sequence the common difference is equal to 2.the first ...

Maths - An arithmetic and a geometric sequence have the same first terms.(2).......

Maths - Eric thinks of 2 sequences.One is geometric and the other arithmetic....

algebra - Consider all 3-term geometric sequences with first term 1 and with ...

Maths - Consider all 3-term geometric sequences with first term 1 and with ...

Math - Consider all 3-term geometric sequences with first term 1 and with common...

geometric sequence - The sum of the 2nd and 5th terms of a geometric sequence is...

math - Determine whether each sequence is arithmetic or geometric. Find the next...